Felix Siauw, Hanan Attaki dan Fenomena Microcelebrity Muslim di Indonesia - Sulistia Salsabiilaa; Aulawiyah Hidayati; Siti Tasliyah; Dhia Fauzan; Abdul Fadhil (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
In contemporary preaching, the use of media is very important and necessary to encourage Muslims to consistently listen to sermons. Felix Siauw and Hanan Attaki conduct their preaching through social media (microcelebrity). This research uses a descriptive qualitative method to answer the researcher's questions about the use of social media as a medium for preaching, the preaching style and messages of Felix Siauw and Hanan Attaki through social media, and the impact and influence of their preaching (microcelebrity) on their followers. The research results show that Felix Siauw and Hanan Attaki also have distinct preaching styles. For example, Felix Siauw focuses more on discussing current political and social issues, while Hanan Attaki emphasizes the development of an individual's spirituality, especially among the younger generation. Both have successfully attracted a large following through relevant content, engaging communication styles, and the use of technology